2005
DOI: 10.1007/s00467-005-2002-x
|View full text |Cite
|
Sign up to set email alerts
|

Grandparent donors in paediatric renal transplantation

Abstract: The outcome of transplantation from grandparent donors in comparison with parental donors in paediatric renal transplantation was evaluated in 53 living related donor (LRD) transplantations performed between January 1996 and August 2003. The donor in 13 cases (25%) was a grandparent (Gpar group), and the remaining donors formed the parent group (Par group). The median age of recipients in the Gpar group was 2.75 (1.7-10.6) years and in the Par group was 12.75 (2.4-22) years (P<0.0001). There was no evidence of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 20 publications
0
8
2
Order By: Relevance
“…A number of adult studies have reported that increasing age of the donor is associated with worse graft survival in both DD and LD recipients . In contrast, some adult and pediatric studies have reported good long‐term graft outcomes irrespective of donor age, including in recipients of kidneys from older donors . There was no significant association between the donor age and graft outcomes in our study either for the whole cohort or separately for LD and DD transplants recipients.…”
Section: Discussioncontrasting
confidence: 80%
See 1 more Smart Citation
“…A number of adult studies have reported that increasing age of the donor is associated with worse graft survival in both DD and LD recipients . In contrast, some adult and pediatric studies have reported good long‐term graft outcomes irrespective of donor age, including in recipients of kidneys from older donors . There was no significant association between the donor age and graft outcomes in our study either for the whole cohort or separately for LD and DD transplants recipients.…”
Section: Discussioncontrasting
confidence: 80%
“…[13][14][15] In contrast, some adult and pediatric studies 7,16,17 have reported good long-term graft outcomes irrespective of donor age, including in recipients of kidneys from older donors. [18][19][20] There was no significant association between the donor age and graft outcomes in our study either for the whole cohort or separately for LD and DD transplants recipients. In one study, 7 transplant outcomes in pediatric patients were only worse from LDs of 55 years or older which could explain our findings given the small number of donors of this age group in our cohort.…”
Section: Predictors Of Graft Failurecontrasting
confidence: 59%
“…This concept of early planning to extend re-transplant options may also have been a factor at play in Victoria where a higher proportion of LD came from grandparents. A previous analysis of graft outcome after LD kidney transplantation in Victoria found no difference in graft survival for LD transplants from grandparent versus other LD (11). Other papers show little overall effect of donor age on LD graft outcomes (12).…”
Section: Discussionmentioning
confidence: 97%
“…A disadvantage, however, is reported for the use of older DD kidneys on graft survival, which is significant between the reference donor age of 15–24 yr and donors aged 45 yr and older . This disadvantage may be further exaggerated with increased HLA mismatches . Reduced time on dialysis may offset some of this disadvantage , but teasing out the relative importance of these factors requires further study.…”
Section: Discussionmentioning
confidence: 99%
“…Long‐term outcome data for grandparents as donors for children with ESRD are scarce, with only a few publications 4‐6 . The observation time varies from two to 20 years and shows satisfactory GS.…”
Section: Introductionmentioning
confidence: 99%